Blizzard in the big data world - how snowflake´s data cloud impacts the cloud data warehousing market - Machado, Ricardo Alberto Baptista Vieira Pimenta (2021)
Data is becoming a driving force of enterprise’s everyday decisions. We felt engaged to perform this Equity Research on Snowflake due to the rising interest of investors in this firm and on the growing market of Data Warehousing. Our consolidated report starts by analyzing overall firm, the competitive landscape of the Cloud Data Warehousing market and the opportunities and challenges the company and market face ahead. This report will cover the aforementioned topics and how they affect the firm’s valuation. The remaining topics of the consolidated report are the company’s discounted cash flow valuation of the future free cash flows to the firm and the main features that valuation model